2019
DOI: 10.1017/s1355617719000468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concussion in Adolescent Students: Perceptions and Performance

Abstract: Objective: The purpose of this study was to compare adolescent students with and without concussion on a battery of academic, neurocognitive, and socioemotional measures and assess the aftereffects of concussion across domains of functioning. Methods: Twenty-four adolescents (ages 13–17) reporting postconcussion symptoms were compared to 24 controls matched for age and gender across a battery of tests and surveys. Results: After correcting for multiple comparisons, there were no significant differences on any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
1
16
1
Order By: Relevance
“…They described how they did not feel like themselves after concussion but found it difficult to explain the feeling. This is consistent with research that found adolescents who experienced a concussion felt something was wrong with them (Rieger, Lewandowski, Potts, & Shea, ). These findings suggest evaluating the effects of the concussion symptoms on adolescents’ lives is important in understanding the symptom experience and developing a management plan.…”
Section: Discussionsupporting
confidence: 90%
“…They described how they did not feel like themselves after concussion but found it difficult to explain the feeling. This is consistent with research that found adolescents who experienced a concussion felt something was wrong with them (Rieger, Lewandowski, Potts, & Shea, ). These findings suggest evaluating the effects of the concussion symptoms on adolescents’ lives is important in understanding the symptom experience and developing a management plan.…”
Section: Discussionsupporting
confidence: 90%
“…Providing academic and psychological support when needed during recovery is important, as academic and mood concerns have been associated with persistent symptoms. 44 Failure to treat these contributing factors may lead to continuing symptoms erroneously being attributed to the persistent pathophysiology of concussion. • If a discussion about sport-related catastrophic outcomes is warranted, be sure to put this in proper context and clearly emphasize its rarity.…”
Section: Implications For Concussion Clinical Managementmentioning
confidence: 99%
“…In another scenario, a student experiencing difficulty with organizational skills or working memory may benefit from using a planner or following written instructions when completing an assignment (Halstead et al, 2013). The intent of AA is to limit symptom recurrence, but it can also decrease a student's anxiety over missed schoolwork during the recovery process (Ransom et al, 2016;Rieger et al, 2019).…”
Section: Perceptions Of General Concussion Knowledgementioning
confidence: 99%
“…These support strategies, or academic adjustments (AA), are chosen based on the student's symptoms and functional deficits and are intended to limit symptom exacerbation after the student's re-integration to the school environment and classroom (Halstead et al, 2013;McAvoy, Eagan-Johnson, & Halstead, 2018). To promote whole person care, health care professionals are encouraged to recommend specific AA when the student returns to school after concussion (Lumba-Brown et al, 2018;Rieger, Lewandowski, Potts, & Shea, 2019). Teachers are thereby tasked with integrating AA for a symptomatic student and noting improvements or declines throughout the student's recovery (McAvoy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%